Plan nowego ogrodu użytkowego W Gołuchowie z roku 1876 - Ławniczak, Grażyna (My University, 2023)
lany parku gołuchowskiego i kwietników ogrodnika Adama Kubaszewskiego znane są z publikacji. Odnaleziony "Plan nowego ogrodu warzywnego z otoczeniem" w Muzeum Narodowym w Poznaniu, wskazuje na dawny ogród w Gołuchowie położony po wschodniej stronie od Zamku, znalazł on omówienie w niniejszym artykule. Wykonany został przez Adama Kubaszewskiego, który był zatrudniony w Gołuchowie od października 1876, jako ogrodnik pracował tam 51 lat. W opisie "Planu nowego ogrodu warzywnego z otoczeniem" urządzanego od roku 1877, wykorzystane zostały Rękopisy Adama Kubaszewskiego – dzienniki prac ogrodniczych w dwóch zeszytach: od 1876 do 1883 i przepisywane później notatki z lat 1888-1903, które znajdują się w Bibliotece Ośrodka Kultury Leśnej w Gołuchowie. "Plan nowego ogrodu warzywnego z otoczeniem" narysowany przez Adama Kubaszewskiego w 1876 roku określa kierunki prowadzenia upraw. Opis ogrodu poszerzony został o historię uprawianych roślin według treści Rękopisów. Zasadniczo wiedza o ogrodzie zamkowym w Gołuchowie, który przedstawiał wszystkie działy ogrodnictwa, przekazana została przez Adama Kubaszewskiego w jego książkach i artykułach popularyzujących nowoczesne ogrodnictwo. Na przedstawionym "Planie nowego ogrodu warzywnego z otoczeniem" udokumentowany został "Dawny ogród owocowy francuski", który w trakcie zakładania nowego ogrodu użytkowego został zachowany. Za jego murami hodowano drzewa owocowe espalier. Wnętrze tego ogrodu ze szklarnią południową przy północnym murze, najstarszym z dawnego ogrodzenia, przypisać należy siedemnastowiecznej lokalizacji lub starszej giardino secretto. Przestrzeń dawnego ogrodu użytkowego w Gołuchowie aktualnie służy celom edukacji przyrodniczej prowadzonej przez Ośrodek Kultury Leśnej. W tym miejscu założone zostały regularne kwatery z roślinnością opracowaną tematycznie. The garden layout for the Gołuchów park and the flower beds completed by the gardener Adam Kubaszewski has been made known following a number of publications on the subject. The document "The blueprint for the new vegetable garden with its surroundings”, newly found in the National Museum in Poznań, indicates its location on the east side of Gołuchów Castle and is discussed in this article. The blueprint was created by A. Kubaszewski, who had been employed at Gołuchów as the gardener since October 1876 and had worked within this capacity for 51 years. In the blueprint’s description of the garden, that had been cultivated since 1877, two documents have been used, namely The Manuscripts authored by Adam Kubaszewski himself, a kind of a gardener’s logbook with its daily entries describing all garden works and contained in two volumes spanning the years between 1876 and 1883-; and later re-written notes made between 1888 and 1903 that are currently held in the library of the Forest Culture Centre at Gołuchów. "The blueprint for the new vegetable garden" drawn up by Adam Kubaszewski in 1876 defines the directions involved in the projected cultivation of vegetable crops. The description of the garden was then expanded to include an account of the history of the cultivated plants according to the content of The Manuscripts. It has to be emphasized that all the knowledge on the castle garden at Gołuchów in all its manifestations has been basically passed down to us in what we can find in Adam Kubaszewski’s books and articles popularising and propagating the idea of modern gardening. The discussed "Blueprint…" documents the existence of the former "French fruit garden” that had been preserved while the setting up of the new kitchen garden was on its way. Behind its walls, free standing espalier fruit trees were cultivated. The interior of the garden with the south greenhouse near the north wall, the oldest preserved wall of the former perimeter fence, has to be ascribed to its original location in the seventeenth century or to even earlier giardino secretto. The inner space of the former vegetable garden at Gołuchów is currently used by the Forest Culture Centre for natural education purposes. The garden in its present form features orderly spaces with thematically detailed vegetation.
A garden blueprint for the new vegetable garden at Gołuchów in 1876
Keywords: Gołuchów; sztuka ogrodowo-parkowa 19 wiek; historia ogrodnictwa polskiego; szkółki drzew 19 wiek; park and garden art in the nineteenth century; history of Polish horticulture in the nineteenth century; nurseries of young trees - 19th